Enhanced Recovery Protocol Enhances Postdischarge Recovery After Laparoscopic Sacrocolpopexy. Issue 2 (February 2022) - Pan, Christine; Hale, Douglass; Heit, Michael
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:667–671) ERAS (enhanced recovery after surgery) guidelines were published in the United States for multiple surgical specialties, including gynecology in 2016. Previous studies on ERAS have focused on the immediate perioperative period.